2023
DOI: 10.33094/ijaefa.v15i1.761
|View full text |Cite
|
Sign up to set email alerts
|

Improving MSME performance through financial literacy, financial technology, and financial inclusion

Abstract: Financial literacy is one of the key abilities and skills MSME business actors require to manage their finances and achieve successful business performance. This study's purpose was to analyze the impact of financial and technological literacy on improving MSME performance in Medan City and the mediation of this relationship by financial inclusion. The research had a quantitative descriptive methodology with an explanatory research approach. Data were collected from a sample of 100 business actors in Medan Cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 4 publications
0
11
0
2
Order By: Relevance
“…The study of Alshehadeh et al, (2023) recommends that Jordanian banks, in light of global competitiveness and the global trend towards digital transformation, follow the financial technology approach and make the most of the opportunities and advantages offered by digitization to banks in order to preserve their customers and compete. According to Gunawan et al, (2023) the results showed that financial literacy, financial technology, and financial inclusion affected the performance of MSMEs in Medan City, and financial inclusion did not mediate the effects of financial literacy and financial technology on the performance of MSMEs in Medan City.…”
Section: Introductionmentioning
confidence: 93%
“…The study of Alshehadeh et al, (2023) recommends that Jordanian banks, in light of global competitiveness and the global trend towards digital transformation, follow the financial technology approach and make the most of the opportunities and advantages offered by digitization to banks in order to preserve their customers and compete. According to Gunawan et al, (2023) the results showed that financial literacy, financial technology, and financial inclusion affected the performance of MSMEs in Medan City, and financial inclusion did not mediate the effects of financial literacy and financial technology on the performance of MSMEs in Medan City.…”
Section: Introductionmentioning
confidence: 93%
“…Bank Indonesia suggests that fintech could potentially assume certain roles traditionally held by banks. Fintech has the potential to enhance business opportunities, facilitate more efficient investments, mitigate risks associated with conventional payment systems, and enable individuals and organizations to save, borrow, and engage in equity investments (Gunawan et al, 2023).…”
Section: Literature Review a Financial Technologymentioning
confidence: 99%
“…With fintech, it will speed up and simplify the process of payments and transactions in the creative industry. Digital payment platforms such as e-wallets, mobile banking and online payment gateways have replaced traditional payment methods such as checks or conventional bank transfers (Gunawan et al, 2023). This enables creative industry players to receive payments more efficiently and securely from their customers around the world.…”
Section: Journal Of Internationalmentioning
confidence: 99%